The Incorporation and Resistance of the Danmei Subculture - Su, Yiqi (Connexion: Journal of Humanities and Social Sciences, 2023)
The Danmei subculture, emerging from Chinese fandom culture and influenced by Japanese Yaoi culture, centers around male-male romantic and/or sexual relationships in fictional narratives across various media. This research article explores the incorporation and resistance of the Danmei subculture within popular culture, with a focus on the internet’s role as a facilitator. The study employs participatory observation and interactive engagement with 121 female Danmei fans to examine ideological and commercial incorporation, as well as the subculture’s impact on gender norms and power dynamics. The findings reveal how Danmei challenges traditional gender and societal norms, fosters inclusivity and acceptance, critiques power imbalances, and promotes participatory culture. The commercial incorporation of Danmei has led to increased visibility but also raises concerns about commodification and cultural authenticity. The research contributes to a better understanding of subcultural dynamics and the significance of female Danmei fans’ experiences in shaping contemporary popular culture.